Pemanfaatan Energi Terbarukan Dengan Menerapkan Smart Grid Sebagai Jaringan Listrik Masa Depan: Pemanfaatan Energi Terbarukan Dengan Menerapkan Smart Grid Sebagai Jaringan Listrik Masa Depan - Denny Haryanto Sinaga; Riz Rifai Oktavianus Sasue; Harvei Desmon Hutahaean (ZETROEM, 2021)
Nowadays Indonesia is facing the challenges with the very high growth of electrical energy needs. The increased has not been followed by the growth of power generation. Various policies have been carried out by the government include the use of renewable energy, which refers to Presidential Decree No. 5 in 2006 on National Energy Policy by setting the contribution target of renewable energy in the national primary energy mix by 17% in 2025 and electricity projects of 35,000 MW. However the focus of policy is not to touch the electricity management sector that actually has a large contribution in performing electrical energy savings. One of them is the implementation of smart grid systems. Smart grid is a continuation of the current system to the next generation vision that combines the use of sensors, communications, computing and control capabilities in some form to improve the overall functioning of the electricity distribution system. Smart grid technologies is the key to use energy resources efficiently distributed. Moreover the smart grid may encourage the application of renewable energy through distributed generation massively. The main focus in this paper is to discuss the prospects, opportunities and challenges in the implementation of smart grid in power distribution systems to improve efficiency and accelerate the use of renewable energy in Indonesia.